Implementasi SISKOMDIG dan Pelatihan Visualisasi Digital sebagai Upaya Transformasi Menuju Smart Village - Alawiyah, Tuti; Hikmah, Agung Baitul; Fatah, Haerul; Al Harits, Atyla Azfa; Fauziyyah, Wafa (Journal of Social Responsibility Projects by Higher Education Forum, 2024)
Serang Village, Tasikmalaya Regency, faces challenges in optimally utilizing digital marketing among MSME actors who are members of the Serang Village Digital Community Space. Most MSME actors still have limitations in displaying products attractively and utilizing digital platforms for marketing. To answer this problem, the community service program together with the Serang Village Digital Community Space partners designed and implemented the Serang Village SISKOMDIG application as a digital community information system that helps manage MSME members that support communication and collaboration between members. In addition, the team provides digital product visualization training such as creating attractive product photos, editing photos and videos, and creating logos to MSME actors so that they are able to improve the visualization of their products on digital platforms. The purpose of this program is to equip MSME actors with skills that strengthen the visual appeal of products in digital marketing, so that they can expand market reach and increase product competitiveness. The results of this program include the implementation of the Serang Village SISKOMDIG application which can be accessed online and obtain an Intellectual Property Rights (IPR) certificate, the training that has been provided is expected to improve participants' skills in creating attractive product visuals. This program provides sustainable solutions to strengthen digital marketing for MSMEs through a technology-based approach and skills enhancement, as an effort to support Serang Village towards becoming a digitally independent Smart Village.